الاستلزام الحواري في التّراث البلاغي العربي "أسلوب الاستفهام عند السّكاكي أنموذجا - عزيز, عز الدين; شتوح, زهرة (University of El-oued, 2021)
تسعى هذه الدّراسة وصف الاستلزام الحواري في التّراث البلاغي العربي، من خلال إسهامات السّكاكي في كتابه "مفتاح العلوم" وتحديدا "أسلوب الاستفهام"، فكان الرّجل واعيا بشكل ضمني بهذه الظّاهرة وبكنه المفاهيم الأساسية الّتي تناولها بول غرايس ضمن نظريته في الاستلزام الحواري، فقد تحدّث السّكاكي عن الاستلزام الحواري، ولكن لا من حيث أنّه مفهوما، وإنّما باعتباره إشكالا دلاليا يظهر من حين إلى آخر أثناء الخطاب. وتهدف الدّراسة كشف المعالم الرّئيسة لهذه الظّاهرة عند السّكاكي الذي يمتاز عن غيره في وصفها، والتّدقيق في مناقشة مسائلها من جهة، ووضعها ضمن وصف لغوي شامل من جهة أخرى؛ يهدف من خلاله إلى ضبط العلاقة بين المعنى الصّريح والمعنى المستلزم حواريا، ويقف البحث عند أسلوب الاستفهام كنموذج للدراسة. This study aims to describe the conversational implication in the Arabic heritage through Es’sekaki contributims in his be work “Key of sciences” particularly, “Interrogative style”. In fact, he was implicitly conscious about this phenomenon, and about the basic concepts studied by paut Grice in his theory “conversational implication”. Es’sekaki has spoken dout it not as it is a concept but as a semantic problem that appears from time to time in the speech. This study aims to discover the main aspects of this phenomenon for the Sekaki, who is different from others describing it, besides to discussing it issues in details, and putting it in a comprehensive linguistic description when he aims to determine the relation between the explicit meaning and the conversational implication meaning.
Conversational Implication In The Arabic Rhetorical Heritage “interrogative Style Of Es’sekaki As A Model
مقال. مجلة القارئ للدراسات الأدبية والنقدية. مج04. ع.01. جامعة الوادي
Keywords: الاستلزام الحواري ؛ الاستفهام ؛ ، المعنى الصّريح ؛ المعنى المستلزم; conversational implication, interrogation,meaning, Implicative meaning explicit